EXAMINING ORGANIZATIONAL SOCIALIZATION, PSYCHOLOGICAL CAPITAL AND CAREER DEVELOPMENT AS PREDICTORS OF CAREER INTENTIONS AMONG HOSPITALITY STUDENTS - Derrick Lee (PUPIL: International Journal of Teaching, Education and Learning, 2026)
Internships play a critical role in shaping students’ career intentions, particularly within the labour‑intensive hospitality sector. Drawing on career construction theory, this study examines how organisational socialisation, psychological capital, and perceived career development influence internship satisfaction and intention to pursue a career in the hospitality industry over the next five‑years among hospitality students at Republic Polytechnic, drawing on career construction theory. Using a quantitative cross-sectional survey design, data were collected from 139 students enrolled in the Industry Immersion Programme (IIP) and Talent Advancement Programme (TAP) pathways. The findings revealed positive relationships among organisational socialisation (OS), psychological capital (PC), and perceived career development (CD)constructs. Regression analyses further indicated that PC and CD are significant predictors of both internship satisfaction and long‑term career intention, while OS demonstrated an indirect influence through these factors. The results underscore the importance of strengthening interns’ confidence, resilience, optimism, and career clarity, alongside providing supportive internship environments. The study offers evidence‑based implications for enhancing internship design, supervision, and curriculum practices, contributing to the development of future‑ready graduates and more sustainable talent pipelines in the hospitality sector.